Information model to support sustainable procurement - Akhir, E.A.P. (IEEE Computer Society, 2017)
Sustainable practices which increase awareness of people in industries which deal with environmental issues need to be implemented. However, information that needs to be considered to make informed decision on sustainable procurement is located in different places and comes in different form, either internal or external of the organizations. Thus, there is a strong need to consider this information to be interrelated and put in one place for easy access. The aim of this paper is to consider all of these concerns and develop information model to support sustainable procurement. It is hope that this information model is able to guide buyers in making the most informed decisions. © 2017 IEEE.